Using Role Playing Models to Improve the Speaking Skills of Class II Elementary School Students - Amalia, Sinta; Kuswendi, Uus; Nurfurqon, Faridillah Fahmi (Journal Of Educational Experts (JEE), 2024)
This research aims to determine the improvement in speaking skills of class II elementary school students using the role playing model, students' responses to learning using the role playing model to improve students' speaking skills and teachers' obstacles in learning using the role playing learning model to improve participants' speaking skills. educate. This research uses a mix method with a sequential explanatory design. The subjects in this research were 38 class II students at an elementary school in Bandung Regency, consisting of 20 male students and 18 female students. The instruments used were pretest and posttest oral tests, student response questionnaire sheets and teacher and student interviews. The research results show that the role playing learning model is quite effective in improving students' speaking skills. This is proven by the results of the n-gain analysis of 73%, as well as the average score obtained by students from the pretest and posttest process , which was initially 51.97%, increased to 87.50%. The response given by students to learning using the role playing model obtained a score of 81% and was in very good qualifications. Meanwhile, the obstacles faced by teachers in learning are at the stage of conditioning students, requiring a long time, and directing students to appear in front of the class.